The story of life - Rooney , Anne; Hues , Nat (London Arcturus, 2019)
Where did the first cells come from? If we evolved from monkeys, why are there still monkeys? How did birds take flight? Explore one of the most incredible ideas in modern science...how natural selection has given rise to the mind-boggling diversity of life on Earth today.'
Science
Keywords: Evolution (Biology)